The great mogul diamond - Taylor, G. P. (Taylor, G. P. Dopple Ganger chronicles, 2010)
When an anonymous note threatens someone they love, twins Sadie and Saskia Dopple are thrust into a series of crimes that look suspiciously like something from the pages of a mystery novel.